Relationship between lifestyle and lifestyle-related factors in a rural–urban population of Japan - Zhang, Shi-chen (Springer Japan, 2012)
OBJECTIVE: To clarify the actual state of residents’ lifestyle in a mixed rural–urban area in Japan, and to investigate the relationship between residents’ lifestyle and lifestyle-related factors. METHODS: The Japanese version of Health Promoting Lifestyle Profile-II (HPLP-II), lifestyle-related factors developed through group work with residents of Town A, and demographic variables were used to evaluate 1176 community residents’ lifestyles and associated factors. RESULTS: Factor analysis revealed that there were 4 factors related to healthy lifestyle. Nonparametric analysis revealed that female and elderly groups showed higher overall HPLP-II score than male and young groups. A significant correlation coefficient was seen between scores of overall HPLP-II and lifestyle-related factors (r = 0.611, p < 0.001). Multiple linear regression analysis demonstrated that HPLP-II was significantly associated with each lifestyle-related factor, showing a similar order in both gender and age groups. Finally, covariance structure analysis demonstrated that the score of health cognition and regional factors increased the score of HPLP-II, which then increased the score of self-rated health. CONCLUSIONS: The present research clarified the actual state of residents’ lifestyles by age and gender in a mixed rural–urban area in Japan, demonstrating a vector model from health cognition and regional factors to self-rated health, via residents’ lifestyle.